The Colossian controversy : wisdom in dispute at Colossae - DeMaris, Richard E. (Journal for the study of the New Testament. Supplement series, 1994)
Identifying the group or position that the author of Colossians attacks in ch 2 of that letter has long occupied scholars, but no interpretative consensus has resulted. This study details the inadequacy of existing reconstructions and offers in their stead the portrait of philosophically inclined Gentiles drawn to the Jewish community and then to the Christian congregation by ideas and practices congenial with their view of the world. Central to the Colossian philosophy's outlook was the pursuit of divine knowledge or wisdom through (1) the order of the cosmic elements (2.8, 20); (2) the bodily.